Bilateral vessel-outlining carotid artery calcifications in panoramic radiographs: an independent risk marker for vascular events - Garoff, Maria (BMC Cardiovasc Disord, 2019)
BACKGROUND: In odontology, panoramic radiographs (PRs) are regularly performed. PRs depict the teeth and jaws as well as carotid artery calcifications (CACs). Patients with CACs on PRs have an increased risk of vascular events compared to healthy controls without CACs, but this association is often caused by more vascular events and risk factors at baseline. However, the risk of vascular events has only been analyzed based on the presence of CACs, and not their shape. Thus, this study determined if the shape of CACs in PRs affects the risk of future vascular events. METHODS: The study cohort included 117 consecutive patients with CACs in PRs and 121 age-matched controls without CACs. CAC shape in PRs was dichotomized into bilateral vessel-outlining CACs and other CAC shapes. Participants were followed prospectively for an endpoint of vascular events including myocardial infarction, stroke, and vascular death. RESULTS: Patients with bilateral vessel-outlining CACs had more previous vascular events than those with other CAC shapes and the healthy controls (p < 0.001, χ(2)). The mean follow-up duration was 9.5 years. The endpoint was reached in 83 people. Patients with bilateral vessel-outlining CACs had a higher annual risk of vascular events (7.0%) than those with other CAC shapes (4.4%) and the controls (2.6%) (p < 0.001). In multivariate analysis, bilateral vessel-outlining CACs (hazard ratio: 2.2, 95% confidence interval: 1.1–4.5) were independent risk markers for the endpoint. CONCLUSIONS: Findings of bilateral vessel-outlining CACs in PRs are independent risk markers for future vascular events.